Sjögren–Larsson Syndrome: A Case Report of a Rare Neuro-cutaneous Disorder - Pradhan, Manish; Giri, Arun; Rai, Dipa; Yadav, Rajeev (Nepalese Medical Journal, 2019)
Sjögren–Larsson syndrome is a rare autosomal recessive neuro-cutaneous disease. The dominant features are congenital ichthyotic hyperkeratosis, spastic diplegia and mild to moderate mental retardation. The cause of this syndrome is the deficiency of microsomal fatty aldehyde dehydrogenase. The deficiency of this enzyme results in the accumulation of fatty aldehydes and fatty alcohols in various tissues including skin. Here, we report a case presented with ichthyosis, bilateral lower limb spasticity, and mental retardation, diagnosed as Sjögren–Larsson syndrome.